Improving Understanding of Climate Change Through "Climate Change Training" for Junior High School Students - Mahananto; Arum, Mutiarra Ridyo; Arbianti; Prasetyowati, Kusriani; Wiyono (Journal of Community Capacity Empowerment, 2024)
Climate change is an important educational issue that contributes to sustainable development. Students in urban areas play an important role as key contributors in mitigating the worsening climate change. This activity aims to increase the understanding of climate change among junior high school students in urban areas. The method used is a classical face-to-face approach with socialization and games using climate flashcards to convey information related to climate change. The evaluation results showed that the students' average knowledge of climate change reached 74.3%, but there was a lower understanding, namely 34.6%, related to adaptation and mitigation efforts. This finding shows that although the students' knowledge level is quite high, a comprehensive understanding of climate change is still lacking. Through this training, an increase in students' understanding of 93% was recorded, indicating that the socialization and game method using climate flashcards was effective in improving students' comprehensive knowledge of climate change. Therefore, this "understanding of climate change" training can be an effective model for climate change education for students